2017
DOI: 10.1093/jnci/djw259
|View full text |Cite
|
Sign up to set email alerts
|

21-Gene Recurrence Score and Locoregional Recurrence in Node-Positive/ER-Positive Breast Cancer Treated With Chemo-Endocrine Therapy

Abstract: Background: The 21-gene recurrence score (RS) predicts risk of locoregional recurrence (LRR) in node-negative, estrogen receptor (ER)-positive breast cancer. We evaluated the association between RS and LRR in node-positive, ER-positive patients treated with adjuvant chemotherapy plus tamoxifen in National Surgical Adjuvant Breast and Bowel Project B-28. Methods: B-28 compared doxorubicin/cyclophosphamide (AC X 4) with AC X 4 followed by paclitaxel X 4. Tamoxifen was given to patients age 50 years or older and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
86
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 117 publications
(92 citation statements)
references
References 20 publications
4
86
2
Order By: Relevance
“…In the cohort of patients with node‐positive disease who participated in the NSABP B‐28 trial and received tamoxifen plus adjuvant chemotherapy (randomized to docetaxel, doxorubicin, and cyclophosphamide or dose‐dense doxorubicin and cyclophosphamide followed by dose‐dense paclitaxel [dd AC‐P] or dd AC‐P with gemcitabine added to paclitaxel), the RS result was shown to be a significant predictor of outcome for disease‐free and overall survival, distant recurrence‐free interval, and breast cancer‐specific survival. Multivariable analysis showed that the RS result was independent of other prognostic indicators, including the number of nodes, tumor size, tumor grade, treatment, and whether or not the patient had a mastectomy .…”
Section: Discussionmentioning
confidence: 97%
“…In the cohort of patients with node‐positive disease who participated in the NSABP B‐28 trial and received tamoxifen plus adjuvant chemotherapy (randomized to docetaxel, doxorubicin, and cyclophosphamide or dose‐dense doxorubicin and cyclophosphamide followed by dose‐dense paclitaxel [dd AC‐P] or dd AC‐P with gemcitabine added to paclitaxel), the RS result was shown to be a significant predictor of outcome for disease‐free and overall survival, distant recurrence‐free interval, and breast cancer‐specific survival. Multivariable analysis showed that the RS result was independent of other prognostic indicators, including the number of nodes, tumor size, tumor grade, treatment, and whether or not the patient had a mastectomy .…”
Section: Discussionmentioning
confidence: 97%
“…6,8 According to a recent analysis of outcomes in patients with ER-positive breast cancer who underwent mastectomy without PMRT for 1 to 3 positive lymph nodes in National Surgical Adjuvant Breast and Bowel Project trial NSABP B-28, the locoregional recurrence rate was only 6% in the subset with high Oncotype Dx (Genomic Health, Inc, Redwood City, CA) recurrence scores, and was even lower for subsets with lower recurrence scores. 11 These data suggest that biologic factors may help to identify women who will derive a greater benefit from PMRT than others. However, a lack of consistency in identifying these subsets in the era of modern surgical and systemic therapies has likely resulted in highly variable treatment patterns across the United States.…”
Section: Introductionmentioning
confidence: 92%
“…Despite the randomized trial evidence in support of PMRT, large single‐institution series have demonstrated low rates of locoregional recurrence in low‐risk subsets of patients with 1 to 3 positive lymph nodes, ranging from 2% to 5% at 5 years . According to a recent analysis of outcomes in patients with ER‐positive breast cancer who underwent mastectomy without PMRT for 1 to 3 positive lymph nodes in National Surgical Adjuvant Breast and Bowel Project trial NSABP B‐28, the locoregional recurrence rate was only 6% in the subset with high Oncotype Dx (Genomic Health, Inc, Redwood City, CA) recurrence scores, and was even lower for subsets with lower recurrence scores . These data suggest that biologic factors may help to identify women who will derive a greater benefit from PMRT than others.…”
Section: Introductionmentioning
confidence: 99%
“…Prediction of prognosis in chemotherapy‐treated patients was validated for the RS in the NASBP B28, PCAS‐01, for Prosigna in the DBCG77B trial . and for Endopredict in the GEICAM/9906 trials . The prognostic power of Mammaprint in untreated patients was validated in the TRANSBIG study .…”
Section: Introductionmentioning
confidence: 99%